A new fabrication method of designed metamaterial based on a 3D-printed structure for underwater sound absorption applications. (28th February 2023) - Baena, Juan Carlos; Wang, Cheng; Fu, Yifeng; Kabir, Imrana I.; Yuen, Anthony Chun Yin; Peng, Zhongxiao; Yeoh, Guan Heng
Highlights: A new fabrication method is proposed based on a 3D-printed structure for underwater-sound absorption. A substantial improvement in the sound absorption was achieved with the designed metamaterial. Metamaterials printed with 82-TPU have more stable sound absorption values with the pressure change. Abstract: Effective sound absorption in a broad frequency range of thin-anechoic materials is a challenge that acoustic materials for underwater applications are still facing. This study proposes a thin-anechoic membrane for underwater applications with an innovative fabrication method for a designed metamaterial based on a 3D-printed structure with a cone-shaped cavities array. The structure is printed with thermoplastic polyurethane (TPU) and cast in a thermoset polyurethane (SPU). Three types of TPUs with different hardness were used to assess the contribution of the polymer properties to the sound absorption performance in the frequency range from 1.5 kHz to 7 kHz and hydrostatic pressure conditions from normal pressure to 1.5 MPa. The materials were characterised using FTIR, FESEM, tensile and compression testing. The FTIR results evidenced a shift of the peak absorption from 1727 cm −1 to 1701 cm −1 when the hardness of the TPU is increased, suggesting a more reinforced network structure that enhances the mechanical properties. The SEM images provided an understanding of the matrix condition given by the 3D-printing parameters, evidencing cavity characteristics that affect the filament adhesion and the mechanical response. Compression testing evidenced the strain-value change of the materials under compression stress and consequently its stability under hydrostatic pressure from 0 MPa to 1.5 MPa. The metamaterial with the designed structure shows a significant improvement in the sound absorption coefficient and more stable coefficient values under hydrostatic pressure when the 82-TPU was used in the 3D-printed structure.